2020
DOI: 10.1371/journal.pone.0226311
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous indocyanine green dye is insufficient for robust immune cell labelling in the human retina

Abstract: It is not currently possible to reliably visualise and track immune cells in the human central nervous system or eye. Previous work demonstrated that indocyanine green (ICG) dye could label immune cells and be imaged after a delay during disease in the mouse retina. We report a pilot study investigating if ICG can similarly label immune cells within the human retina. Twelve adult participants receiving ICG angiography as part of routine standard of care were recruited. Baseline retinal images were obtained pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…This may indicate successful ICG platelet-labeling stability in survival and recovery studies in vivo. ICG stability in serum and its non-targetability are commonly described challenges and are required to be tested in vivo [45,46]. Here, we present a successful and stable ICG labeling of platelets in WB ex vivo as a proof of concept for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate successful ICG platelet-labeling stability in survival and recovery studies in vivo. ICG stability in serum and its non-targetability are commonly described challenges and are required to be tested in vivo [45,46]. Here, we present a successful and stable ICG labeling of platelets in WB ex vivo as a proof of concept for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of light guidance and molecular targeting for precise drug delivery may have unexpected surprises. For instance, we noticed a clinical trial that tries to label immune cell in the human retina [71], meaning that specific cell therapy based on PS might be possible. In clinical practice, a class of PS drugs represented by ICG is mainly used for clinical diagnosis, such as surgical navigation of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is proof of concept in mouse that infiltrating cells can be actively imaged with ICG (Sim et al, 2015) however, imaging immune cells in deeper retinal layers or the heavily pigmented choroid will necessitate the use of fluorescent labels. Previous studies have demonstrated that ICG could label infiltrating leukocytes in a laser-induced CNV mouse model of age-related macular degeneration (AMD) after depot administration (Sim et al, 2015), but intravenous ICG was insufficient to detect immune cell labelling in the human eye (Bell et al, 2020).…”
Section: Tnc Is Actively Taken Up Into Cd4 + T-cells and Can Be Image...mentioning
confidence: 99%